ENHANCING DISTANCE LEARNING: A CASE STUDY OF THE HISTORY OF PHYSICAL CULTURE COURSE (Physical Culture and Sport: Scientific Perspective, 2025)
The digital transformation of higher education has led to the widespread adoption of distance and blended learning formats, particularly in response to the COVID-19 pandemic. These changes have raised new challenges for the teaching of humanities disciplines, including the History of Physical Culture, which plays a crucial role in shaping students’ professional identity and intercultural competence. Despite the growing interest in digital education, methodological approaches to teaching this discipline in an online format remain underexplored. Purpose. This study aims to analyze the experience of designing and implementing a distance course on the History of Physical Culture, assess its effectiveness in developing professional and intercultural competencies, and propose improvements for online teaching methodologies. Methods. The study involved 67 first-year students and employed mixed methods, including literature analysis, observation, student surveys, and statistical data processing. The course was delivered via MOODLE, incorporating asynchronous content, synchronous discussions, interactive tools, and project-based learning. Results. Students positively evaluated the course’s structure, interactivity, and accessibility. Asynchronous access to materials allowed for flexible learning, while synchronous sessions facilitated engagement. Key challenges included self-organization and the need for more contemporary sports-related examples. Conclusion. The study confirms the effectiveness of the blended approach in humanities education. Future improvements should focus on expanding multimedia content, refining assessment methods, and enhancing self-regulation support. These findings provide a framework for optimizing digital humanities instruction in sports education and beyond.
Keywords: digital pedagogy; intercultural education; asynchronous learning; student self-organization; interactive tasks